VERDI AND WAGNER IN EARLY VICTORIAN LONDON: THE VIEWPOINT OF “THE MUSICAL WORLD” - Massimo ZICARI (Studia Universitatis Babeş-Bolyai. Musica)
As early as 1844, Henry Fothergill Chorley, one of the most authoritative figures of Victorian journalism, drew attention to two young composers, Giuseppe Verdi and Richard Wagner, whose recent success could not escape the critic’s attention. However, while Verdi’s operas made their regular appearance in London over the decades following Ernani’s premier at Her Majesty’s Theatre in 1845, it was not until 1870 (with L’Olandese Dannato, alias Der Fliegende Holländer) that the first full performance of a dramatic work by Wagner was given in the English capital city. Notwithstanding this disparity, a first glance at the reviews that appeared in The Times, The Musical World, The Athenaeum, The Sunday Times and The Spectator, and that were then reproduced in the columns of The Musical World, shows the extent to which, between 1845 and 1855, both composers became object of severe critical scrutiny. By the mid-1850s Wagner’s figure was conceptualized on the basis of factors that only in part depended on the quality of his music; yet, the manner in which his controversial writings impinged on the Victorian musical milieu benefited Verdi’s image, which came to be understood as a more reassuring popular composer.